Challenging mass incarceration in the City of Care: Punishment, community, and residential placement - Brown, Elizabeth (Theoretical criminology, 2018)
Challenges to mass incarceration often come from places seeking to bolster "community" sanctions and community-based alternatives to punishment. In the City of Care, local community activists challenged growing rates of juvenile incarceration and the overrepresentation of youth of color in juvenile detention by advocating for a community-based "circle of care". These efforts resulted in the local juvenile court embracing the "least restrictive interventions". In cases where juveniles could not be helped "in the community", residential placement replaced the practices of sending young people to juvenile hall or the California Youth Authority. This article examines how the use of placement sought to unseat the ethos of punishment, but inadvertently incentivized young people to stay in juvenile hall. Thus, in the City of Care the extension of "community-based" services is often no different from practices of punishment, and must be interrogated as part of the state repertoire of control and exclusion.